2011 24th International Symposium on Computer-Based Medical Systems (CBMS) 2011
DOI: 10.1109/cbms.2011.5999156
|View full text |Cite
|
Sign up to set email alerts
|

An embedded mobile deductive system for low cost health monitoring support

Abstract: Home-based health monitoring systems are currently being used to support early detection of abnormal conditions and prevention of its serious consequences. Many patients can benefit from continuous ambulatory monitoring as a part of a diagnostic procedure, optimal maintenance of a chronic condition or during supervised recovery from an acute event or surgical procedure. An evolution of this approach is the use of the mobile infrastructure and wearable technology, which mainly provides more freedom to their use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…In fact, despite technology advances, we found that in several cases batteries do not last long enough to cover an entire work day in such circumstancese.g. Siebra et al (2011), Warren et al (2011), Pandey et al (2012), Lagerspetz and Tarkoma (2011), Alamri (2012). The remote processing of data is a growing trend as we shall see later in section 3.10.…”
Section: Hardware Infrastructurementioning
confidence: 98%
See 2 more Smart Citations
“…In fact, despite technology advances, we found that in several cases batteries do not last long enough to cover an entire work day in such circumstancese.g. Siebra et al (2011), Warren et al (2011), Pandey et al (2012), Lagerspetz and Tarkoma (2011), Alamri (2012). The remote processing of data is a growing trend as we shall see later in section 3.10.…”
Section: Hardware Infrastructurementioning
confidence: 98%
“…65%) used prototypes to test the solutions. Among those studies, half of them (13) focused on patient monitoring (Fernandes et al, 2011;Catarinucci et al, 2012;Chi et al, 2010;Heslop et al, 2010;Ivanov et al, 2010;Lara et al, 2012;Pandey et al, 2012;Masse et al, 2010;Pigadas et al, 2011;Siebra et al, 2011;Soomro and Schmitt, 2011;Al-Taee et al, 2011;O'Brien et al, 2010).…”
Section: Early Classification Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents have the role towards conducting information analysis, decision making in terms of communication, strategies for energy consumption, urgent alerts, and delivery of health procedures and so on. Secondly, do more information analysis based on historical information and apply robust intelligent mechanism such as data mining, diagnosing and so forth depending on the supervision of medical experts" (Siebra et al 2011).…”
Section: Agents In Patient Health Monitoring and Medical Recordmentioning
confidence: 99%
“…The sensor networks are currently being employed in a variety of applications. For example, military probes, monitor of water quality, biomedical monitor and etc [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%